Kinship and Beyond: The Genealogical Model Reconsidered - Ryan Schram (Ethnobiology Letters, 2010)
Review of Kinship and Beyond: The Genealogical Model Reconsidered. Sandra Bamford and James Leach, eds. 2009. Berghahn Books, New York. 292 pp., 21 illustrations, bibliography, index. $95.00 (hardback). ISBN 9781845454227.